Daños estructurales y reforzamiento en la Iglesia Católica Señora del Carmen-Guayaquil - Castillo Rugel, Taiz Viviana (2024)
The Nuestra Señora del Carmen Church in the city of Guayaquil is part of the cultural heritage, it has 85 years of construction, since its creation it has taken care of adequate maintenance, particularly affecting the structure, aesthetics, stability and resistance of the building . The general objective was to analyze the wooden floors as an alternative to reinforce the structural damage of the Nuestra Señora del Carmen Catholic Church in the city of Guayaquil. The referential framework is made up of references from theorists and the relevance of cultural heritage in the construction of the church studied. In particular, wood is presented as a structural element, timber species, advantages and disadvantages, as well as ductility, and seismic vulnerability. In the research methodology, the deductive method was applied, starting from the general to the particular, with a descriptive scope that allowed structural reinforcement to be carried out through the use of wooden floors and to understand the structural damage through a detailed inspection. The survey technique was applied to the workers of the Church, the object of the study, the results of which identify the need to propose reinforcement with wooden floors on levels one, two and three of the North Tower and South Tower. In conclusion, in the investigation it was detected that when wood is used for construction it changes significantly, particularly when it is used to build the floors for beams and joists that form the reinforcement with techniques for the settlement of the metal beam.